TRANSFORMATIVE PUBLIC SPEAKING: DA'WAH AS A MEDIUM FOR EMPOWERING THE COMMUNITY - Safril; Rahayu Rahmadini; Amrullah; Arifah; Doni Muhamad Julianto (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Public speaking is a strategic communication skill in supporting the effectiveness of da'wah. From a contemporary perspective, da'wah is no longer merely understood as conveying normative messages, but also as a means of empowering the community. This article aims to analyze the relevance of transformative public speaking as a da'wah medium that is not only informative, but also participatory and drives social change. The research method used is a literature study with a descriptive-analytical approach. The results of the study indicate that transformative public speaking is able to integrate aspects of ethos, pathos, and logos in da'wah communication so that da'i can build credibility, engage the audience's emotions, and convey logical arguments that encourage critical awareness. Da'wah based on transformative public speaking has implications for increasing the spiritual, intellectual, and social capacity of the community. These findings emphasize that da'wah in the digital era needs to be oriented towards strengthening the capacity of the community through transformative public speaking skills.